2017
DOI: 10.1097/md.0000000000006838
|View full text |Cite
|
Sign up to set email alerts
|

The value of APACHE II in predicting mortality after paraquat poisoning in Chinese and Korean population

Abstract: Background:The Acute Physiology and Chronic Health Evaluation II (APACHE II) score is used to determine disease severity and predict outcomes in critically ill patients. However, the prognostic significance of APACHE after acute paraquat (PQ) poisoning remains unclear. The meta-analysis was aimed to study the value of APACHE II in predicting mortality in PQ-exposed Chinese and Korean patients.Methods:Databases that included PubMed, Embase, Cochrane Library, and the Chinese National Knowledge Infrastructure wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
(40 reference statements)
1
32
0
1
Order By: Relevance
“…The APACHE II score was found to be useful in predicting mortality in patients with intoxication, urosepsis, and ICU admission (2,8,10,11). Furthermore, high APACHE II scores were found to be associated with prolonged ICU hospitalization (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The APACHE II score was found to be useful in predicting mortality in patients with intoxication, urosepsis, and ICU admission (2,8,10,11). Furthermore, high APACHE II scores were found to be associated with prolonged ICU hospitalization (9).…”
Section: Discussionmentioning
confidence: 99%
“…For an APACHE II score with a low threshold (≥5), the sensitivity and specificity in predicting mortality was 75% and 86%, respectively. In contrast, for an APACHE II score with a high threshold value (≥10), significantly higher sensitivity (84%) and specificity (88%) values were reported (11). Özbilgin et al reported that the sensitivity and specificity of an APACHE II score >13.5 in predicting mortality was 77.5% and 70.9%, respectively (3).…”
Section: Discussionmentioning
confidence: 99%
“…The SICU patients had a median baseline SOFA score of 4 (IQR, 3-9) and a median APACHE II score of 16 (IQR,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). A significant cutoff point for SOFA score has not yet been established, although SOFA score cutoffs in predicting mortality are reported to range from 2 to 7.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] APACHE II score cutoffs of 10-24 are reported to have high sensitivity and specificity in predicting clinical outcomes. [16][17][18] Considering the roles of SOFA and APACHE II scores in determining disease severity, the SICU patients in the present study were regarded as having moderately severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, several prognostic score systems have been reported to predict the clinical outcomes of patients with PQ poisoning, the major ones being the Acute Physiology and Chronic Health Evaluation II (APACHE II) score [7], Sequential Organ Failure Assessment (SOFA) score [8], the severity index of PQ poisoning (SIPP) [9], Poisoning Severity Score (PSS) [10] and some equations and nomograms based on large cohort study [11][12][13]. Most of them are more suitable for critically ill patients instead of minimally poisoned or early-stage patients who showed mild symptoms.…”
Section: Introductionmentioning
confidence: 99%